Construction of Seven Contiguous Chiral Centers by Two Methods: Quadruple Michael Addition vs Stepwise Double‐Double Michael Addition Controlled by Adding Speed of Michael Acceptor. Issue 10 (15th July 2016) - Ozeki, Minoru; Hayama, Noboru; Fukutome, Shintaro; Egawa, Honoka; Arimitsu, Kenji; Kajimoto , Tetsuya; Hosoi, Shinzo; Iwasaki, Hiroki; Kojima, Naoto; Node, Manabu; Yamashita, Masayuki
Abstract: A tandem "quadruple" Michael addition reaction of (+)‐bornylamide with two equivalents of a Michael acceptor having two α, β‐unsaturated ester moieties spontaneously proceeded to afford one diastereomer with seven contiguous chiral centers in 27 % yield. Meanwhile, a stepwise "double‐double" Michael addition, in which the very slow addition of the first one equivalent of the acceptor substrate to the bornylamide was followed by a further addition of another Michael acceptor bearing two α, β‐unsaturated ester moieties, provided a compound with a similar set of seven contiguous chiral centers on a different carbon skeleton in 48 % yield. Both quadruple and double‐double Michael adducts were one of 128 possible diastereomers, namely, each Michael addition in those two reactions proceeded in 72 % and 83 % yields on average, respectively. We showed the importance of adding speed of the Michael acceptor to the bornylamide in controlling the quadruple and double‐double Michael addition reactions. Abstract : Seven contiguous chiral centers were finely constructed by two different methods: a tandem "quadruple" Michael addition and a stepwise "double‐double" Michael addition of (+)‐bornylamide. The adding speed of the Michael acceptor to (+)‐bornylamide markedly influenced the way the reactions proceeded in different directions. The very slow addition induced the formation of a reactive enolate intermediate that finally afforded a double‐double Michael adduct, whereas the normal addition yielded a quadruple Michael adduct.